اللاجئون السوريون بين الحماية واللجوء : ألمانيا أنموذجا - الزقيبة، أحمد عقيل محمد (جامعة الإسكندرية - كلية الحقوق, 2018)
تناولت هذه الدراسة الأزمة السورية وما تمخض عنها من نزوح أعداد كبيرة من المواطنين السوريين، ولجوئهم إلى مختلف دول العالم؛ ومنها جمهورية ألمانيا الاتحادية؛ طلبا للأمن والحماية. وقد تعرضت الدراسة للقوانين والاتفاقيات الدولية التي تنظم الوضع القانوني للاجئين، ومنها الوثيقة التي كتبت بعد الحرب العالمية الثانية والخاصة بحقوق الإنسان، ومن الاتفاقيات الهامة كذلك اتفاقية عام ١٩٥١ التي تعتبر الأداة العالمية الملزمة لحماية اللاجئين، ويمثل هذه الاتفاقية المفوضية السامية للأمم المتحدة لشؤون اللاجئين (UNHCR). كما تناولت الدراسة مدى التزام الدول المستضيفة للاجئين بهذه القوانين والاتفاقيات الدولية التي تحفظ للاجئين حقوقهم، وتصون كرامتهم الإنسانية. وقد تبين من خلال هذه الدراسة أنه في بداية أزمة اللجوء السوري كانت أغلب الدول الأوروبية تتجاهل لائحة دبلن وتمنح طالبي اللجوء حرية أكبر في اختيار الدولة التي يرغبون في اللجوء إليها. وقد تلقى اللاجئون السوريون مع بداية وصولهم ألمانيا معاملة خاصة تمثلت في الحصول على استحقاقات حكومية، ومع ارتفاع أعداد اللاجئين، وبعد الهجمات الإرهابية التي نفذت في عدد من الدول المستضيفة للاجئين السوريين، وبروز أحزاب اليمين المتطرفة، وانقسام الأحزاب السياسية في ألمانيا بين مؤيد لسياسة الباب المفتوح أمام اللاجئين السوريين وبين معارض لها.
This study investigated the Syrian crisis that led to the displacement of large numbers of Syrian people, and their emigration to the countries of the world, in order to request asylum, Including Germany, to seek security and protection. This study examined the laws and international conventions governing the legal status of refugees, including the Human Rights Document that was recorded after the Second World War. This study also addressed the 1951 Convention as one of the most important conventions and the first international legally binding document explicitly related to the protection of refugees, represented by the United Nations High Commissioner for Refugees (UNHCR). The study also investigated the extent of the commitment of the host countries to these laws and international conventions that preserve the refugees' rights and protect their human dignity. This study found that at the beginning of the Syrian asylum crisis, most European countries ignored the Dublin Regulation and granted asylum seekers greater freedom to choose the state they wish to immigrate to Upon their arrival to Germany, Syrian refugees received special treatment from the government and got benefits, including the right to family reunification and the right to work. However, with the increase in the number of refugees; the terrorist attacks carried out in a number of countries hosting Syrian refugees; the rise of extreme right-wing parties; the division of political parties in Germany between supporters and opponents of ‘the open door policy’ to Syrian refugees.
Keywords: القوانين والتشريعات -- المعاهدات والمواثيق الدولية -- حقوق الإنسان -- القضايا الإنسانية -- اللاجئون السوريون -- سوريا -- المجتمع السوري -- مستخلصات الأبحاث